A bHLH-type transcription factor, JA-ASSOCIATED MYC2-LIKE1, acts as repressor to negatively regulate jasmonate signaling in Arabidopsis - Nakata, Masaru (2013)
Jasmonates (JAs) are plant hormones that regulate the balance between plant growth and responses to biotic and abiotic stresses. Although recent studies have uncovered the mechanisms for JA-induced responses in Arabidopsis thaliana, the mechanisms by which plants attenuate the JA-induced responses remain elusive. Here, we report that a basic helix-loop-helix-type transcription factor, ABA-INDUCIBLE BHLH-TYPE TRANSCRIPTION FACTOR/JA-ASSOCIATED MYC2-LIKE1 (JAM1), acts as a transcriptional repressor and negatively regulates JA signaling. Gain-of-function transgenic plants expressing the chimeric repressor for JAM1 exhibited substantial reduction of JA responses, including JA-induced inhibition of root growth, accumulation of anthocyanin, and male fertility. These plants were also compromised in resistance to attack by the insect herbivore Spodoptera exigua. Conversely, jam1 loss-of-function mutants showed enhanced JA responsiveness, including increased resistance to insect attack. JAM1 and MYC2 competitively bind to the target sequence of MYC2, which likely provides the mechanism for negative regulation of JA signaling and suppression of MYC2 functions by JAM1. These results indicate that JAM1 negatively regulates JA signaling, thereby playing a pivotal role in fine-tuning of JA-mediated stress responses and plant growth.